From the Sea to Politics: Masonry in New Spain/Mexico, 1816-23 - Vázquez Semadeni, María Eugenia (2013)
The origins of Freemasonry in Mexico have always been surrounded by myths and mysteries, mainly due to the scarcity of Masonic documents to clarify them. In this paper, these origins and the socio-economic groups to which itsmembers belonged are discussed based on primary sources recently found. The paper also addresses when and why the early Mexican Freemasonry was involved in the country’s political life.